Objective and Long-Term Evaluation of the Efficacy and Safety of a 1064-nm Picosecond Laser With Fractionated Microlens Array for the Treatment of Atrophic Acne Scar in Asians - Woraphong Manuskiatti (2022)
Background and Objective: Fractional 1064-nm picosecond-domain laser has recently been utilized for the treatment of atrophic acne scars and showed promising results. However, data on the safety and efficacy of this procedure in dark-skinned patients are limited. This prospective, self-controlled study was conducted to objectively evaluate the safety and efficacy of a 1064-nm picosecond laser coupled with a microlens array (MLA) for the treatment of atrophic acne scars on Asian skin. Study Design/Materials and Methods: Twenty-six subjects of Fitzpatrick skin types (FSTs) III and IV with atrophic acne scars were enrolled. All subjects were treated with a 1064-nm picosecond laser (spot size of 8 mm, fluence of 1.0 J/cm2, a repetition rate of 10 Hz) in combination with the MLA handpiece for an average of three passes, for 6 monthly sessions. Objective (measurement of scar volume using three-dimensional (3D) photography and skin roughness analysis using ultraviolet A-light video camera) and subjective (clinical evaluation by two blinded dermatologists) assessments were obtained at baseline and at 1, 3, and 6 months after the final treatment. Results: Statistically significant reduction of the scar volume from baseline at 1, 3, and 6 months after the final treatment were observed by 3D photography and ultraviolet A-light video camera. At the 6-month follow-up, 50% (13 of 26) of the subjects were rated as having at least 50% improvement of the scars. The rate of improvement significantly increased from the 1-month follow-up to the 6-month follow-up (P = 0.013). Similarly, at the 6-month follow-up, the scar volume (P = 0.024) and skin roughness (P = 0.001) also significantly improved, in comparison with the baseline. Mild postinflammatory hyperpigmentation (PIH) was observed to develop in approximately 18% of all the treatment sessions. All cases of PIH were temporary and resolved within 4 weeks on average. Conclusions: The 1064-nm picosecond laser with MLA is a safe therapeutic alternative for the treatment of atrophic acne scars in dark-skinned individuals. Lasers Surg. Med. © 2020 Wiley Periodicals LLC.